The attitudes of UTAR students towards learning English as a second language - Fam, Wen Wei (2025)
This study explores the attitudes of Universiti Tunku Abdul Rahman (UTAR) undergraduate students towards learning English as a second language, examining the relationship between students' attitudes and their proficiency levels, and investigating potential gender differences. Using a quantitative research design, data were collected through a questionnaire adapted from Gardner’s (1985) Attitude and Motivation Test Battery (AMTB). A total of 103 students participated, categorised based on their Malaysian University English Test (MUET) proficiency levels. The findings reveal that students generally have positive attitudes towards learning English as a second language. A significant relationship was found between higher proficiency levels and more positive attitudes. However, no statistically significant gender differences were identified. The study emphasises the importance of improving English proficiency to foster positive attitudes and recommends interventions that support low-proficiency learners. The findings provide insights into language education strategies and contribute to the broader understanding of second language acquisition among Malaysian university students.